PENEGAKAN HUKUM TERHADAP PELAKU PENIPUAN ONLINE MENGGUNAKAN IDENTITAS PALSU MENURUT KITAB UNDANG-UNDANG HUKUM PIDANA DIHUBUNGKAN DENGAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI - Yana Kusnadi Srijadi (Program Studi Magister Ilmu Hukum Pascasarjana Universitas Langlangbuana, 2021)
ABSTRACT Fraud crime is currently growing in line with the times and technological advances. Legal regulations are made to anticipate this, but the existing regulations do not appear to have reduced the crime but have increased. This study aims to: first, examine law enforcement against online fraud using a false identity; and second, knowing the inhibiting factors and the efforts made in criminal law enforcement against online fraud crimes using false identities. This research was conducted using the normative juridical method, namely legal research carried out by reviewing and examining secondary data in the form of positive law, especially in the field of criminal law related to Law Enforcement Against Online Fraud Perpetrators Using False Identities According to the Criminal Code Associated with the Law Law Number 19 Year 2016 Concerning Amendments to Law Number 11 Year 2008 Concerning Electronic Information and Transactions through library research by examining secondary data including statutory regulations, research results, scientific journals and references. The results of the study illustrate that the criminal act of online fraud using a false identity is the same in principle as conventional fraud, but the difference lies in the evidence or means of action, namely using electronic systems (computers, internet, telecommunication devices). Therefore, law enforcement regarding online fraud using a fake identity can still be accommodated by the Criminal Code and Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions, only seen from fulfillment of the elements as well as the meaning of the word fraud still does not meet the rules of legal certainty. Furthermore, obstacles in law enforcement against fraud based on electronic transactions are still influenced by five factors, namely legal factors, law enforcement factors, facilities or facilities that support law enforcement, community factors and cultural factors. Keywords: Law Enforcement, Online Fraud, Fake Identity